Use of Magnetic Resonance Imaging in the Evaluation of Acute Cholecystitis in Emergency Setting - Sharma, U. K.; Thapa, D. K.; Thapaliya, S.; Pokhrel, A.; Baskota, B.; Rai, U. (Kathmandu University Medical Journal, 2022)
Background Acute cholecystitis is one of the commonest surgical disease. The rapid diagnosis at its early stage is one of the crucial factor in patient care and management.Objective To evaluate the role of magnetic resonance imaging (MRI) and magnetic resonance cholangiopancreatography (MRCP) in the diagnosis or exclusion of acute cholecystitis, coexisting choledocholithiasis, and acute pancreatitis in emergency setting.Method This study was conducted in the department of radiodiagnosis B&C teaching hospital, Birtamod, Nepal from July 2016 to November 2019. Patients, clinically diagnosed as acute cholecystitis or biliary condition with positive Murphy’s sign with or without jaundice and deranged Liver Function Test, raised Leucocyte counts were evaluated by Magnetic Resonance imaging. The sensitivity, specificity, Positive Productive Value (PPV), Negative Productive Value (NPV) were calculated for the diagnosis of acute cholecystitis. Data was entered and analysed by using SPSS version 20. Result There were 40 patients included in our study. Among them 27 (67.5%) were females and 13 (32.5%) male. The age of the patients ranged from 16 years to 79 years, mean age 49.4 years. Majority of the patients were in the age group of 40-60 years (57.5%). The overall sensitivity, specificity, Positive Productive Value and Negative Productive Value of Magnetic Resonance imaging diagnosis of acute cholecystitis were 100%, 66.6%, 94.4% and 100% respectively. Acute cholecystitis associated with gall stone disease were common and found in 72.5% cases, with sensitivity 96.5%, specificity 27.7%, Positive Productive Value 77.7% and Negative Productive Value 75.0%.Conclusion Magnetic resonance imaging (MRI)/Magnetic resonance cholangiopancreatography (MRCP) is an excellent tool for the evaluation of biliary pathology and can be used for the preoperative evaluation of acute cholecystitis at the emergency setting.